Binocular Vision Problems in Refractive Surgery Patients: Vision Therapy Case Reports. - Day, Gina; Powers, Maureen K.; Faktorovich, Ella (Optometry & Visual Performance, 2015)
Background: Some post-LASIK patients complain of blurry distance vision months after refractive surgery, despite good corneal healing and negligible refractive error. We postulated that perceiving blur in the absence of refractive error or significant monocular aberrations might result from poor binocular control. Binocular vision testing in a series of such patients revealed convergence problems in 83% of cases. Case Reports: We report on 8 patients (average age 37.4 yrs) who completed up to 40 sessions of vision therapy (VT), either completely via computer or in a combination of computer orthoptics and office vision therapy. Seven patients had received LASIK; one had PRK. Optometric measurements and symptoms were recorded before and after VT treatment, starting at least 3 months after refractive surgery. Near point of convergence improved in 7 cases following VT, and convergence break and/or recovery improved in 6 cases. Six cases reported symptom reduction, and pre-presbyopic cases tended to improve accommodative facility. The number of binocular functions showing improvement per case correlated with the number of VT sessions completed. Convergence changes were statistically significant when pre-/post-VT data were compared for these cases as a group. Conclusion: Patients complaining of distance blur following refractive surgery may have undiagnosed binocular vision problems. VT incorporating an internet orthoptics component improved convergence ability in the cases reported here, and most patients reported symptomatic relief.